Novel λ3‐Iodane‐Based Functionalization of Synthetic Carbon Allotropes (SCAs)—Common Concepts and Quantification of the Degree of Addition. Issue 50 (24th October 2014) - Hof, Ferdinand; Schäfer, Ricarda A.; Weiss, Cornelius; Hauke, Frank; Hirsch, Andreas
Abstract The covalent functionalization of carbon allotropes represents a main topic in the growing field of nano materials. However, the development of functional architectures is impeded by the intrinsic polydispersibility of the respective starting material, the unequivocal characterization of the introduced functional moieties, and the exact determination of the degree of functionalization. Based on a novel carbon allotrope functionalization reaction, utilizing λ3‐iodanes as radical precursor systems, we were able to demonstrate the feasibility to separate and to quantify thermally detached functional groups, formerly covalently linked to carbon nanotubes and graphene through thermogravimetric GC‐MS.